Água virtual e o complexo soja: Contabilizando as exportç\~oes brasileiras em termos de recursos naturais - Camillo de Moraes Bassi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The text aims to account for Brazilian exports, in terms of natural resources. Precisely, the virtual water, carried by soy complex in 2013, identifying the volumetric addition, the main recipients. The proposal, more than the simple quantification, is to demonstrate that, as Brazil is a major exporter of food, thus also stands at the level of fresh water; that, in this condition, supports substantial portion of the water needs of others, presenting, therefore, to its trading partners, as a complementary source of the resource in question
Keywords: Q25; Q56; 330; virtual water; soybean; natural resources; international commerce